Sunspots and starspots - Thomas, John H. 1941- (Cambridge University Press, 2008)
The past two decades have seen remarkable advances in observations of sunspots and their magnetic fields, in imaging of spots and fields in distant stars and in associated theoretical models and numerical simulations. This book provides a comprehensive combined account of the properties of sunspots and starspots. It covers both observations and theory, and describes the intricate fine structure of a sunspot's magnetic field and the prevalence of polar spots on stars. The book includes a substantial historical introduction and treats solar and stellar magnetic activity, dynamo models of magnetic cycles, and the influence of solar variability on the Earth's magnetosphere and climate. This volume is a valuable reference for graduate students and specialists in solar and stellar physics, astronomers, geophysicists, space physicists and experts in fluid dynamics and plasma physics.